Apparency revisited. Issue 1 (27th August 2015) - Strauss, Sharon Y.; Cacho, N. Ivalú; Schwartz, Mark W.; Schwartz, Ari C.; Burns, Kevin C.
Abstract: How easy a plant is to find, or its apparency, is thought to shape plant defenses. Recent meta‐analyses suggest that the types of plant defenses employed are not well‐predicted by apparency, or apparency can be confounded with life history traits like woodiness and stature. Here, we suggest that the searching environments in which plants grow also influence plant apparency and should thus affect investment in plant defense. Specifically, bare, unvegetated environments may result in greater apparency of inhabitants of all statures to enemies, as a result of loss of associational resistance. We make several predictions about plant defenses in simple searching environments. (1) Plants living in simple searching environments should be more highly defended than plants living in more vegetated, complex searching environments. (2) Plant defenses involving signals—both, signals serving to hide plants and aposematic signals—should be favored in simple searching environments. (3) Levels of damage from enemies in simple searching environments should be related to defensive strategy (resistance, aposematism, mimicry, or crypsis); apparent plants should have low damage, because, as they are easily found, they should be well‐defended though physical or chemical defense. In contrast, predictions about damage levels in cryptic plants are harder to make, as damage reflects both whether plants are encountered or not, as well as overall palatability. If crypsis is favored in more palatable species, as has been suggested previously, we predict that cryptic plants should have greater variance in damage and greater maximum damage, if, once found, plants are palatable. (4) Organisms from diverse evolutionary lineages inhabiting the same simple searching environments should adapt to selection from apparency by converging on similar background matching or aposematic defenses. We then test some of these predictions with descriptive data collections in two simple searching environments: largely unvegetated graywacke scree mountaintops of New Zealand and serpentine barrens of northern California (USA). We find that plants that are more apparent (i.e., do not match local rock color as measured across 300–700 nm wavelengths) are more defended, as inferred from mean damage received. In contrast, cryptic species in the same habitats get 7× more heavily damaged, once found, suggesting overall greater palatability. There was no evidence of greater variation in damage, as measured by coefficient of variation, but maximum damage was much greater on cryptic species in both habitats. Convergence on gray substrate is found in diverse species of plants in New Zealand, as well as by scree‐living grasshoppers; in California, grasshoppers have also converged on substrate color, and seed color of a non‐cryptic plant also matches local outcrops. Considering searching environment and enemy searching abilities when evaluating plant apparency to enemies may shed more light on this challenge to plants.